2022
DOI: 10.1021/jacs.2c02442
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Threshold between Fullerenes and Nanotubes: Characterizing Isomerically Pure, Empty-Caged, and Tubular Fullerenes D5h-C90 and D5d-C100

Abstract: We report the fully fledged photophysical characterization of isomerically pure, empty-caged, tubular fullerenes D 5h -C 90 and D 5d -C 100 and compare their key properties. In particular, the focus was on cage sizes between 60 and 150 carbon atoms with D 3 , D 3d/h , and D 5d/h symmetry. The optical band gap of D 5d -C 100 is 1.65 eV, which is larger than 1.37 eV of D 5h -C 90 . In stark contrast to the nonluminescent D 5h -C 90 , D 5d -C 100 luminesces at room temperature. Transient absorption spectroscopy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…14 Thus, all studied fullertubes have considerable gaps exceeding at least 1.5-2 eV. The spectra closely resemble those reported in the literature 5,10,11,15 thus confirming the structural identity of studied molecules.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…14 Thus, all studied fullertubes have considerable gaps exceeding at least 1.5-2 eV. The spectra closely resemble those reported in the literature 5,10,11,15 thus confirming the structural identity of studied molecules.…”
Section: Resultssupporting
confidence: 85%
“…In the experimental Raman spectrum it is detected as the medium-intensity feature at 1447 cm −1 . Another C 100 vibration with the large weight of the pentagonal pinch mode is A 1g (15) predicted at 1493 cm −1 . Here the cap and the belt parts contribute equally, each represented by a totally symmetric mode, A g (2) for C 60 and A 1g (2) for CNT.…”
Section: Normal Mode Analysis For C 100 -D 5dmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2021, a study showed a transition to metallic properties by inserting 10 carbon atoms from the shorter [5,5] C 90 -D 5h (1) fullertube to the longer [5,5] C 100 -D 5d (1) fullertube. In 2022, an excited state study of [5,5] C 90 -D 5h (1) fullertubes showed photophysical properties consistent with classical fullerenes. However, the longer [5,5] C 100 -D 5d (1) fullertube broke the trend expected for fullerene behavior and suggested unique properties for C 100 fullertubes.…”
mentioning
confidence: 99%
“…In 2022, an excited state study of [5,5] C 90 -D 5h (1) fullertubes showed photophysical properties consistent with classical fullerenes. However, the longer [5,5] C 100 -D 5d (1) fullertube broke the trend expected for fullerene behavior and suggested unique properties for C 100 fullertubes. A separate study in 2022 evaluated the catalytic behavior of fullertubes .…”
mentioning
confidence: 99%